Entrepreneurial Aptitude of Women of an Aspirational District of Uttarakhand - Jyoti Singh, Jyoti Singh; Anuradha Dutta, Anuradha Dutta; Pratibha Singh, Pratibha Singh; Ankita Dobhal, Ankita Dobhal; Deeba Manan, Deeba Manan; Pooja Goswami (Indian Journal of Extension Education, 2023)
A cross-sectional study was conducted for assessing the entrepreneurial aptitude of women in two blocks (Kashipur and Gadarpur) of Udham Singh Nagar, Uttarakhand. A purposive sampling technique was utilized for selecting the respondents. A structured questionnaire vetted by experts and pretested through a pilot study on 45 respondents was developed. Data on women entrepreneurs, self-assessment, and perception of farm women regarding entrepreneurial aptitude was collected from 214 women during the month of June 2022 to August 2022. Results revealed that only 28.50% of women were running their own enterprises, whereas 40.98% of them were engaged in vegetable production/commercial farming. 89.25% of women were interested in running an enterprise and 84.11% had a motto to earn money. 84.11% of the respondents were interested in backyard poultry and 31.31% in spice production. It was concluded that women in the study area had an aptitude for adopting enterprises for improving their quality of life, which needs to be nurtured.